Generating unfair ratings to attack online rating systems - Liang, Liting. (2011)
Many online voting systems have been developed to help users of the system to make informed decisions in nowadays. However, these systems may be attacked by different attack models. Meanwhile, the attack behavior is greatly influenced by the defense system used. Therefore, this project aims to investigate the detecting ability of each detection algorithm on each attack algorithm. In this paper, our main focus will be on the detection algorithms. For understanding and analyzing the results, this paper will involve the attack algorithms as well.